2007
DOI: 10.1097/moh.0b013e3280ef68f8
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-mediated regulation of platelet signaling pathways

Abstract: Purpose of review-There is considerable interest in understanding the function and mechanism of calpains in platelet aggregation, spreading, and granular secretion pathways. Recent insights from the calpain-1 knockout platelets suggest a pivotal role of these cysteine proteases in the regulation of outside-in signaling, aggregation, and clot retraction.Recent findings-The calpain-1 knockout mouse provided direct evidence for the role of calpain-1 in platelet aggregation and clot retraction. Reduced tyrosine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…Thus, for GPCRs that are extensively coupled to G 13 , such as PAR1, G␣ 13 SR1, and G␣ 13 SR2 signaling events are sequentially induced, where PAR1-mediated activation of G␣ 13 SR1 leads to intraplatelet calcium mobilization (8). This increase in intraplatelet calcium levels then promotes multiple platelet signaling events (29 -31) including binding of G␣ 13 SR2 to whole talin and subsequent cleavage of the talin rod domain, presumably by calpain (32)(33)(34). Once formed, the G␣ 13 SR2-talin head domain complex binds to the ␤3 cytoplasmic tail leading to integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for GPCRs that are extensively coupled to G 13 , such as PAR1, G␣ 13 SR1, and G␣ 13 SR2 signaling events are sequentially induced, where PAR1-mediated activation of G␣ 13 SR1 leads to intraplatelet calcium mobilization (8). This increase in intraplatelet calcium levels then promotes multiple platelet signaling events (29 -31) including binding of G␣ 13 SR2 to whole talin and subsequent cleavage of the talin rod domain, presumably by calpain (32)(33)(34). Once formed, the G␣ 13 SR2-talin head domain complex binds to the ␤3 cytoplasmic tail leading to integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone therapy increased insulin sensitivity (supplemental Table 1) and had profound effects on the platelet proteome ( Figure 1A, supplemental Figure 1, supplemental Table 3). More than half of the differentially expressed protein spots identified were known calpain substrates (eg, talin-1 and filamin A) 13 and could be classified as cytoskeletal proteins and signaling molecules involved in metabolism and vesicle/secretory trafficking. Some of the proteins identified (eg, septin-5, the integrin-linked kinase [ILK] and glycerol-3-phosphate dehydrogenase 2 (GPD2) have not been previously linked with calpain.…”
Section: Proteomic Analysis Of Platelets From Patients With and Withomentioning
confidence: 99%
“…Subsequent experiments were performed with mice lacking the major Ca 2ϩ -dependent cysteine protease, calpain-1 (-calpain, Capn1 Ϫ/Ϫ gene), that accounts for ϳ80% of the calpain activity in mouse and human platelets (37). Assessment of collagen-dependent thrombus formation indicated that the Capn1 Ϫ/Ϫ blood formed enlarged thrombi, which displayed increased integrin ␣ IIb ␤ 3 activation (JON/A mAb binding) but decreased PS exposure (AF647-annexin A5 binding) compared with wild type Capn1 ϩ/ϩ blood (Fig.…”
Section: Closure Of Activated Integrin ␣ Iib ␤ 3 In Ps-exposing Platementioning
confidence: 99%